Rediseño estructura, caracterización y modelamiento CFD del funcionamiento del túnel de viento subsónico de ciclo abierto tipo NPL por succión de 2 Hp de potencia de la Universidad Antonio NariñoDiego Pardo Amaya_Diego Pardo Amaya_ (2021)
Currently, the Antonio Nariño University has an open cycle subsonic wind tunnel, which is out of operation due to the accumulated deterioration of its mechanical and electrical components, in addition, it does not have the documentation that supports the variables and operational parameters of operation, so the purpose of this project is to perform a complete theoretical characterization and modeling of its operation, to check its operating parameters, specifically analyzing variables such as range of pressures generated by changes in flow velocities and aerodynamic coefficients, which can be applied to a CFD simulation in Flow Simulation of SolidWorks, to serve as a frame of reference for the results obtained in a future practice in the field. Additionally, it is intended to propose an improvement in its operation, redesigning the test area and its support structure, which have been identified as having drawbacks and technical failures. Consequently, a tutorial type guide document will be generated, which recreates the CFD simulation so that it can be replicated by students and teachers of the area through a learning experience.